Survey on broadcasting in VANETs - Ahmed, Shereen Ali Malek (Maxwell Science Publications, 2014)
This study aims to evaluate, categorize and compare the Vehicular Ad-hoc Network (VANET) broadcasting protocols. Massive amount of VANET broadcasting protocols have been proposed in the literature. Aiming efficiency, reliability, scalability and reach-ability each of them adopts certain techniques to provide a certain level of functionality. This study distinguishes the VANET routing protocols in several categorizes according to the applications it may serve. By focusing into broadcasting protocols, the study further divides the reviewed algorithms according to the techniques they used to initiate the communication, which would be either through beaconing, handshaking, or instant broadcasting. These protocols are further classified according to the criteria that have been used to select the next forwarder. The criteria usually influenced by the targeted performance of the technique. Such criteria may include furthest node from the sender, the node with the best link quality, endanger nodes, nodes with high probability of forwarding and backbone nodes. Performance metrics that are used for quantitative evaluation are suggested.